National integration and contested autonomy : the Caribbean coast of Nicaragua - Baracco, Luciano (Algora Pub., 2011)
The Indigenous and Afro-descendant peoples along Nicaragua?s Caribbean Coast, once colonized by the British, have long sought to establish their autonomy vis-à-vis the dominant Spanish-influenced regions of the Pacific coast. The book provides a wide overview of the autonomy process by looking at the historical background of autonomy, claims to land, language rights, and land demarcation and communal forestry projects. This book seeks to satisfy the globally emerging interest in the idea of autonomy and bi-zonality as an effective mechanism of conflict resolution and protection of minority rig.